CHARACTER DEVELOPMENT FROM THE VIEWPOINT OF ISLAMIC TEACHINGS - Suryadi, Ahmad; Ondeng, Syarifuddin; Syahruddin, Syahruddin (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
The objective of this article is to examine how character education is viewed in Islamic Education. This study utilises qualitative methods, specifically library research. The data for this study is derived from written materials relevant to the topic. The findings indicate that character education and Islamic education are not in conflict, but rather complement each other in fostering societal growth and promoting a civilised community. The virtues promoted in character education, such as integrity, accountability, patriotism, compassion, peacefulness, acceptance, self-control, innovation, and more, are all encouraged in Islamic doctrine and are traits of individuals who have faith and reverence for Allah SWT.